URBAN REVITALIZATION: STRATEGIES FOR THE RECOVERY OF DEGRADED NEIGHBORHOODS AND SUSTAINABLE DEVELOPMENT (International Seven Journal of Multidisciplinary, 2025)
The revitalization of degraded neighborhoods has proven to be an effective strategy for promoting urban and social development, recovering areas affected by a lack of infrastructure, precarious housing conditions, and insecurity. This process involves not only the construction of new housing but also investments in essential services such as education, healthcare, and public spaces, ensuring sustainable transformation and the inclusion of local populations. However, careful planning is necessary to prevent gentrification, which can displace original residents due to rising living costs. Studies on urbanization projects worldwide highlight that community participation and institutional support are crucial factors for successful revitalization. Initiatives such as the Kibera pilot project in Kenya emphasize the importance of a hybrid model that combines population engagement with structural investments. Other studies highlight the connection between housing improvements and public health promotion, demonstrating that well-planned interventions can reduce inequalities and strengthen social cohesion. Urban renewal can also be driven by the use of sustainable technologies, such as the implementation of renewable energy and economic empowerment programs. Innovative models, such as the redevelopment of degraded housing into modern residential complexes, show that it is possible to improve residents' quality of life without compromising housing accessibility. To ensure the effectiveness of these interventions, they must be institutionalized and integrated into long-term public policies. Therefore, urban revitalization should not be viewed solely as a physical restructuring of spaces but as a broad strategy for social and economic development. When well planned, these initiatives contribute to reducing inequalities, enhancing urban spaces, and improving the overall quality of life for the population.